Analisis Pemahaman Sitasi dalam Meningkatkan Kualitas Penulisan Karya Ilmiah Mahasiswa Akhir di Universitas Islam Negeri Sumatera Utara Medan - Najwa Habiebah; Rizky Amanda Syahfitri Nasution; Zaidan Hamdani; Zainal Abidin (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the understanding of final-year students regarding the use of citation in academic writing at Universitas Islam Negeri Sumatera Utara Medan. This research employed a qualitative method with a phenomenological approach. Data were collected through semi-structured interviews, observation, and documentation involving two final-year student informants from the Faculty of Da’wah and Communication and the Faculty of Ushuluddin and Islamic Studies. The findings indicate that students understand the conceptual function of citation; however, in practice, citation use frequently shifts into a mere administrative formality. Citation errors are attributed to low academic awareness, weak literacy culture, and excessive dependence on reference management applications without a thorough understanding of the cited sources. Insufficient understanding of citation negatively affects the quality and integrity of students’ academic work. This study concludes that improving academic literacy and providing continuous academic writing guidance are essential to enhancing citation practices among final-year students. These efforts can strengthen accurate, responsible, and ethical scholarly writing practices.